Influence of some processing variables on the rheological properties of lithium lubricating greases modified with recycled polymers. (1st January 2012) - Martín-Alfonso, J.E.; Valencia, C.; Sánchez, M.C.; Franco, J.M.; Gallegos, C.
This work deals with the effect that some processing variables and type of mineral lubricating oil (naphthenic and paraffinic) used exert on the rheological properties of lubricating greases modified with recycled polymers. In particular, the optimisation of recycled polymer addition at different lubricating grease processing stages and cooling profiles were studied. The influence of processing variables was evaluated by performing small-amplitude oscillatory shear (SAOS), viscous flow and thermal analysis tests. From the experimental results obtained, it may be concluded that the addition of recycled polymer significantly increases the values of linear viscoelasticity functions, especially when added immediately after the saponification reaction, during the heating stage, or at the beginning of the cooling stage (180°C). A combined stepwise cooling ramp, first at a high rate and then at a low rate, is more effective to achieve higher values of the rheological functions than the application of constant cooling rates in the final processing stage. The values of the rheological functions decrease as base oil viscosity increases and increase when using a naphthenic instead of a paraffinic oil of similar viscosity.